Digital Minimarket Design using the Building Information Modeling Method and Comparison of RISHA and Conventional Time and Costs - Rondonuwu, Yosua Gilberth Cristovel; Pribadi, Richmon A; Tutu, Trifena H; Rasjid, Irgi S; Peginusa, Stefani S; Rumbayan, Rilya (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2023)
This research aims to design a minimarket building using precast concrete and compare the costs and implementation time of precast concrete and conventional concrete. With precast concrete technology using RISHA (Simple Healthy Instant House) panels which are standardized and have been tested by the PUPR Ministry, this helps to simplify and save time on the process of building this minimarket. This advantage makes precast concrete an alternative for use as an alternative construction system. The research method used is experimental in the computer laboratory, Civil Engineering Department, Manado State Polytechnic where the design uses digital methods, namely BIM (Building Information Modeling) technology with Tekla software, and several other supporting applications such as Autocad and Sketchup. The output of this research is a precast concrete minimarket building design product, and it can be concluded that for minimarkets with a building area of 129 m2, the RISHA method can reduce costs, especially for carrying out concrete structural work, by 84% compared to using conventional concrete, with a price difference of IDR 238,411. 660.01. For time comparison, the RISHA method is superior with a difference of 5 days or 35 working hours.